Presence of polyketide synthases and nonribosomal peptide synthetase in culturable bacteria associated with Aplysina fulva and Aplysina caissara (Porifera) - Rojas, Letícia Sanfilippo; de Fernandes, Michelle Guzmán; da Motta, Andressa Cristina Ramaglia [UNESP]; Carminato, Luiza Porteiro [UNESP]; Zanatta, Ana Caroline [UNESP]; Lôbo-Hajdu, Gisele; Jimenez, Paula; Custódio, Márcio Reis; Hardoim, Cristiane Cassiolato Pires (Springer Nature, 2025)
Culture-dependent and -independent studies have provided access to symbiont genes and the functions they play for host sponges. Thus, this work investigates the diversity, presence of genes of pharmacological interest, biological activities and metabolome of the bacteria isolated from the sponges Aplysina caissara and Aplysina fulva collected on the southwestern Atlantic Coast. The genes for Polyketide Synthases types I and II and Nonribosomal Peptide Synthetases were screened in more than 200 bacterial strains obtained, from which around 40% were putatively novel. Twenty-two were positive for at least one of the genes screened. Among them, 12 exhibited antimicrobial activities and one inhibited the proliferation of cancer cells. The metabolic profiles of the 22 strains were analyzed by liquid chromatography with tandem mass spectrometry and molecular network. The Global Natural Products Social Molecular Networking MolNetEnhancer workflow provided a more comprehensive understanding of the metabolic profiles. The results revealed the existence of a wide range of metabolites, however more than half of the compounds could not be identified. It was further observed that the metabolic diversity among the strains varied primarily due to the cultivation medium used. Together the results obtained here revealed the pharmacological potential of the bacteria isolated from Aplysina species.
Keywords: Bioactive compounds; GNPS; Molecular network; NRPS; PKS; Sponges